The Light Judgment Decisionin The Case Of Corruption: The Implications For The Sense Of Public Justice - Oksidelfa Yanto Yanto; Yoyon M Darusman; Ichwani Siti Utami; Nurdiyana Nurdiyana (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
This research purposes to recognize the crime of corruption that occurs can injure the justice of society, then also want to know the lightness of the judge's decision in corruption and its implications for a sense of justice. The research method that I use in this paper is a normative juridical research method by multiplying data sources through documentation research on secondary data. The results of the study show that corruption can harm the justice of society, this is because the perpetrators of corruption have taken people's rights against the law, the perpetrators of corruption hamper the progress of the nation, corruptors corrupt democracy and afflict the people. The lightness of judges' decisions in corruption cases has implications for people's sense of justice. This is because the judge's decision is the crown and the culmination of the reflection of the values of justice, essential truth and human rights. The judge is the spearhead of justice for society.”